PERBANDINGAN EFEKTIVITAS MENTIMUN DAN BELIMBING TERHADAP PERUBAHAN TEKANAN DARAH - Henny Syapitri; Edriyani Yonlafado Simanjuntak (Jurnal Ilmiah Keperawatan, 2019)
Hypertension is a condition when blood pressure in blood vessels increases chronically. Seeing the complexity of the problem of hypertension and the existence of pharmacological treatment of hypertension barriers due to the declining purchasing power of people and having a price that is quite expensive so that non-pharmacological treatment can be a good and useful alternative choice, both in terms of economical (cheap) and affordable. Non-phamacological therapy is by modifying daily patterns and returning to natural products (back to nature). Referring to the concept of back to nature by using local materials that are widely available in the community because these materials are rich in antioxidants and potassium. Cucumbers have potassium and magnesium while star fruit contains potassium and sodium which have an effect on reducing blood pressure. This study aims to compare the administration of cucumber fruit juice with sweet star fruit to the reduction in blood pressure in hypertensive patients. The type of this research is quasy experiment with pre and post test group design.The sampling technique uses purposive sampling technique. Blood pressure is measured using a sphygmomanometer. The results showed a decrease in blood pressure after being given cucumber juice and star fruit. Based on the Independent T test, the P value of 0.653 (P >0.05) shows that there is no significant difference, meaning that between starfruit juice and cucumber can lower blood pressure, so it can be concluded that cucumber and starfruit are equally good at reducing blood pressure in patients hypertension in Posbindu Mekar Sari Helvetia Medan